PENGARUH AUDIT TENURE DAN LOCUS OF CONTROL TERHADAP KUALITAS AUDIT DENGAN INDEPENDENSI SEBAGAI VARIABEL INTERVENING (Studi pada Auditor Inspektorat Daerah Se-Provinsi Sulawesi Tengah) - Dina; Abdul Pattawe; Fikry Karim (APSSAI, 2025)
Research aims: This study examines the effects of audit tenure and locus of control on audit quality, with auditor independence as an intervening variable, among Regional Inspectorate auditors in Central Sulawesi Province, Indonesia. The research is grounded in attribution theory, which explains auditor behavior as a function of internal and external factors. Design/Methodology/Approach: Using a quantitative research approach, data were collected through questionnaires distributed to regional inspectorate auditors and analyzed using structural equation modelling. Research findings: The results reveal that audit tenure has a negative but insignificant effect on auditor independence and does not significantly influence audit quality. These findings indicate that the length of audit engagements in the public sector does not compromise or enhance audit quality, given the mandatory nature of audit assignments, standardized procedures, and strong regulatory frameworks. Conversely, locus of control has a positive and significant effect on both auditor independence and audit quality, suggesting that auditors with a strong internal locus of control are better able to maintain objectivity and produce high-quality audits. Auditor independence is also found to have a positive and significant impact on audit quality and to mediate the relationship between locus of control and audit quality, although it does not mediate the relationship between audit tenure and audit quality. Theoretical contribution/Originality: This study contributes to the public-sector auditing literature by highlighting the dominant role of internal psychological attributes over structural factors in determining audit quality and provides practical implications for auditor development and governance in regional inspectorates.